Menggali Potensi Kecerdasan Anak Melalui Pendekatan Spiritual - Ahmad, Nur (PIAUD Universitas Islam Negeri Sunan Kudus, 2014)
Intellectual and spiritual intelligence are like a coin that cannot beseparated beside emotional intelligence to determine one’s success. However,there is a trend that could determine the top, not only success but alsohappiness. It is spiritual intelligence that will raise our consciousness as theinheritors of the earth. Thus, we will be useful not only for ourselves but also forthe sustainability of the people around us. Spiritual intelligence is not growingas an adult, but must be nurtured and raised and trained from an early ageso that individuals would become superior. Therefore it is very regrettable forparents, because it represents happiness of our children in their life. When thespiritual intelligence is high then someone will easily achieve the happiness.But otherwise it will be difficult ito someone to feel it. How important it is forour next generation (children), because it is the heart or essence of a person’slife purpose human child